Відлуння слова Івана Котляревського в мові художньої прози Павла Загребельного - Голікова, Н. (Культура слова, 2019)
У статті досліджено інтертекстуальну взаємодію стилістем, що в художніх творах І. Котляревського і П. Загребельного репрезентують поняття «сміхова культура». Виявлено мовно- естетичні знаки в епічній бурлескно-травестійній поемі «Енеїда» І. Котляревського, які функціонують як цитати або слугують зразком для творення виражально-зображальних засобів – носіїв гумористичної аксіології в мові романів П. Загребельного. Індивідуально-авторські риторичні фігури прозаїка комплексно проаналізовано в межах лінгвостилістики, етнолінгвістики, теорії інтертекстуальності, літературної ономастики. The article explores the intertextual interaction of stylists, who in the works of I. Kotlyarevsky and P. Zahrebelny represent the concept of «laugh culture». The linguistic and aesthetic signs in the epic burlesque-travesty poem «Aeneid» by I. Kotlyarevsky, which served as a model for the creation of expressive and pictorial means – carriers of humorous axiology in the language of a number of P. Zahrebelny’s novels, are revealed. Attention is drawn to the fact that the foundations for the formation of a ridiculous culture as a genre segment of Ukrainian literature are laid in the poem «Aeneid» by I. Kotlyarevsky, which is written in a syllabic-tonic verse (iamb) – the size most appropriate for the Ukrainian language. The linguistic and literary traditions of ridicule are at the heart of the humorously narrative tonality of P. Zahrebelny’s two novels – «The Lion’s Heart» and «Exile from Paradise», which form the thematic-storyline. It is emphasized that the figure of I. Kotlyarevsky is a significant creative personality for P. Zagrebelny, who often appeals to the creator of the creator of Ukrainian literary language in his prose. The novelist dialogues with the artistic texts of the laughingstock, introducing meaningfully expressive fragments of them into the intersemiotic field of prose works. The intertextual interplay of linguistic components of the individual-linguistic paintings of the world of two writers can be traced in the functional and structural-semantic similarity of a number of style word, which are often the result of stylistic reception of the language game: intertext (linguocultural and ethnolanguage characters), literary and artistic anthroponyms, as well as wordssymbols, which are functionally significant components of the peripheralevaluative sphere. The individual and authorial rhetorical figures of P. Zahrebelny are comprehensively analyzed within the limits of linguistics, ethno-linguistics, theory of intertextuality, literary onomastics. It has been concluded that the linguistic creation of the prose contains an important humorous-axiological segment of artistic narrative, which is organically incorporated into the context of Ukrainian laugh culture.